Analisis Pesan Visual pada Media Kampanye Luar Ruang Caleg 2019 - Nurhablisyah, Nurhablisyah; Susanti, Khikmah (Magenta | Official Journal STMK Trisakti, 2019)
Campaign moment in Indonesia means every place near the road or meeting point was covered by legislative campaign’s banner (out of home media). In 2019, this campaign media was overloaded which could covered others belonging from different party. Not only roads, trees, home’s gate and wall was becoming a random target for placing the media. Another phenomenon that was caught by eyes was too many message attributes which applied into the media by using AIDA Model (attention, interest, desire, action), therefore riders and pedestrian could not see the meaning clearly. Those visual message consists of texts, illustration (photos), color, layout etc. This descriptive research is trying to analyze visual message in legislative out of home media campaign 2019 in East Jakarta and Depok. Analysis method is using out of home principals messages. The result of this research showed, mostly legislative candidates didn’t’ applied the ideals principals about out of home media characters. Designing message for out of home media should base on this principals; (1) out of home provide a very limited information space, therefor choose the most important message and conduct mission and vision,(2) pedestrian and riders don’t have enough time to read all the information, choose the readable and clear text, illustration and color, (3) the frequency and size of the media is also influence the attention, (4) media was not only to attract people but also to influence to people around it.